The association between dog ownership or dog walking and fitness or weight status in childhood. Issue 6 (28th October 2016) - Westgarth, C.; Boddy, L. M.; Stratton, G.; German, A. J.; Gaskell, R. M.; Coyne, K. P.; Bundred, P.; McCune, S.; Dawson, S.
Summary: Background: Health benefits of dog walking are established in adults: dog owners are on average more physically active, and those walking their dogs regularly have lower weight status than those who do not. However, there has been little research on children. Objectives: This study aimed to examine the association between dog ownership or dog walking and childhood fitness or weight status. Methods: A survey of pet ownership and involvement in dog walking was combined with fitness and weight status measurements of 1021 9 to 10‐year‐old children in the Liverpool SportsLinx study. Results: We found little evidence to support that children who live with, or walk with, dogs are any fitter or less likely to be obese than those who do not. Conclusions: This is an important finding, as it suggests that the activity that children currently do with dogs is not sufficient enough to impact weight status or fitness.